IS THE FIRST IMPRESSION THE ONE THAT REMAINS?! IMPRESSIONS AND OPINIONS OF THE ACADEMIC STUDENTS OF PHYSICAL EDUCATION - UFSC (Fiep Bulletin - online, 2014)
"Is the first impression the one that remains?!" This is how the old saying goes. Is it true? Can it maybe be apllied on the academical and professional choice? The impressions, opinions and reflexions presented  here compose a cut of an inquiry, carried through in the second semester of 2004, about the desire and the reality concerning to the expectations of the academics of Licentiateship in Physical Education at UFSC referring to their professional formation. Qualitative methodology was used, and to collect the data half-structuralized interviews and analysis of speeches. Twelve academics of the first and the eighth phases were the subjects of this study. There has been verified that the desire of becoming a professional in the area of Physical Education, usually emerges in the childhood/youth, meaning, to the majority, the pleasure. The desire was influenced by professional models, positive experiences with the Physical Education and mainly with the sport. When reflecting on the impressions of the seniors referring to the course and their abilities, we conclude that if the objectives of the course would be contemplated successfully, we would witness indications of changes that should be, or better, must be spreaded. Their notes, are sorrounded by criticism, politization, they propose improvements, they bring up the importance of some debates which, several times guard the interests of politicians which conduct the the education in Brazil nowadays. When interviewing the freshmen we evidenced that the speeches in this moment are not critical, not political and where the "to like" and the personal satisfaction is what interests, but, we believe that soon, the academics, when being questioned in this same way can have a less individualist opinion, more concerned to the social part, to the society in which "I" am part of and which "I" must act and reflect over.
Keywords: Professional formation; Physical Education; Academic formation